2004
DOI: 10.1038/nbt1025
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable cyan fluorescent protein for protein tracking

Abstract: In recent years diverse photolabeling techniques using green fluorescent protein (GFP)-like proteins have been reported, including photoactivatable PA-GFP, photoactivatable protein Kaede, the DsRed 'greening' technique and kindling fluorescent proteins. So far, only PA-GFP, which is monomeric and gives 100-fold fluorescence contrast, could be applied for protein tracking. Here we describe a dual-color monomeric protein, photoswitchable cyan fluorescent protein (PS-CFP). PS-CFP is capable of efficient photoconv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
265
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(270 citation statements)
references
References 24 publications
0
265
0
5
Order By: Relevance
“…Here, we compare four properties of PAFPs that are critical for superresolution imaging and report two new PAFPs that exhibit excellent performance in all four properties. (14), mEos3.2 (15), tdEos (16), mKikGR (17), PAmCherry (18), PAtagRFP (19), mMaple (20), PSCFP2 (13,21), Dronpa (22), and mGeosM (23). From this screen, we found that none of these PAFPs was simultaneously optimal in all four criteria described above.…”
mentioning
confidence: 88%
“…Here, we compare four properties of PAFPs that are critical for superresolution imaging and report two new PAFPs that exhibit excellent performance in all four properties. (14), mEos3.2 (15), tdEos (16), mKikGR (17), PAmCherry (18), PAtagRFP (19), mMaple (20), PSCFP2 (13,21), Dronpa (22), and mGeosM (23). From this screen, we found that none of these PAFPs was simultaneously optimal in all four criteria described above.…”
mentioning
confidence: 88%
“…Still, photoswitchable proteins have not displayed their full potential, because proteins that are just photoactivatable [11][12][13] can be switched only once, which implies that repeated measurements with the same molecule are impossible. On the other hand, photochromic or reversibly switchable fluorescent proteins (RSFPs) can be repeatedly photoswitched between a fluorescent and a nonfluorescent state by irradiation with light of two different wavelengths.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…They can have emission spectra from cyan at less than 470 nm (Chudakov et al 2004) to red at greater than 600 nm peak emission (Matz et al 1999;Wiedenmann et al 2002;Schnitzler et al 2008). They can also act as chromoproteins (Lukyanov et al 2000), which absorb light to cause a visible colour without producing appreciable fluorescence.…”
Section: Introductionmentioning
confidence: 99%